2002
DOI: 10.1046/j.1365-313x.2002.01395.x
|View full text |Cite
|
Sign up to set email alerts
|

Light regulated modulation of Z‐box containing promoters by photoreceptors and downstream regulatory components, COP1 and HY5, in Arabidopsis

Abstract: SummaryThe Z-box is one of the light-responsive elements (LREs) found in the promoters of light inducible genes. We have studied the light responsive characteristics of Z-box containing synthetic as well as native promoters. We show that promoters with Z-box as a single LRE or paired with another LRE can respond to a broad spectrum of light. The response is primarily mediated by phyA, phyB and CRY1 photoreceptors at their respective wavelengths of light. We have demonstrated that CAB1 and Z-GATA containing pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(93 citation statements)
references
References 66 publications
2
90
0
Order By: Relevance
“…Although several LTREs have been described so far (28)(29)(30), to our knowledge the Z-box is the first cis-regulatory sequence reported that integrates light and cold signaling. Light-induced gene expression mediated by the Z-box, including that of CAB1, depends on HY5 (14). Interestingly, our findings reveal that the cold-induced expression of CAB1 also depends on HY5, suggesting a role for this factor in regulating gene expression in response to low temperature.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Although several LTREs have been described so far (28)(29)(30), to our knowledge the Z-box is the first cis-regulatory sequence reported that integrates light and cold signaling. Light-induced gene expression mediated by the Z-box, including that of CAB1, depends on HY5 (14). Interestingly, our findings reveal that the cold-induced expression of CAB1 also depends on HY5, suggesting a role for this factor in regulating gene expression in response to low temperature.…”
Section: Discussionmentioning
confidence: 58%
“…Our data show that the Z-box, in addition to mediating light-induced gene expression (14), also mediates CAB1 expression in response to low temperature and constitutes an LTRE. Although several LTREs have been described so far (28)(29)(30), to our knowledge the Z-box is the first cis-regulatory sequence reported that integrates light and cold signaling.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The DNA-binding assays were performed as described by Yadav et al (2002) at room temperature in a final volume of 25 mL of binding buffer [15 mM HEPES, pH 7.5, 35 mM KCl, 1 mM EDTA, 6% glycerol (v/v), 1 mM dithiothreitol, 1 mM MgCl 2 , and 0.5 mg poly(dI-dC)]. The samples were incubated at room temperature for 15 min and later run on a 5% polyacrylamide gel at 12 to 15 mAmp.…”
Section: Electrophoretic Mobility Shift (Gel-shift) Assaymentioning
confidence: 99%
“…binding site (Cheong et al, 1998). The HY5 protein interacts with both the G-(CACGTG) and Z-(ATACGTGT) boxes of the light-regulated promoter of RbcS1A (ribulose bisphosphate carboxylase small subunit) and the CHS (chalcone synthase) genes Chattopadhyay et al, 1998;Yadav et al, 2002). To test whether STF1 and HY5 have similar DNA-binding properties, the binding properties of each were compared with eight different DNA sequences that represent G-, C-, and C/G-box motifs (Fig.…”
Section: Stf1 Can Replace Hy5 In Photomorphogenesis and Hormone Signamentioning
confidence: 99%